A smart field management computerised system prototype for immature and mature oil palm plantation - Dani, Norizawati; Nair, Vikneswaran; Daud, Mohamed (Universiti Putra Malaysia, 1999)
Oil palm being a very sensitive crop requires close monitoring and good field management for optimum production. All immature and mature oil palms require intense field upkeep and management. Some of the routine upkeep and management are on weed control, fertilisation, pest and disease control and also pruning. Keeping track of these routine chores can be tedious in large estates with small number of personnel. A smart field management computerised system can be developed to efficiently and effectively manage every single point from immature up to mature oil palm. The system will be able to monitor and give progress report with up-to-date costing for each item of the upkeep and other field management. In addition, this smart computerised system will be able to monitor the budgeted cost for each item of the field upkeep and management. The system will also have a complete database of pest and disease diagnosis and treatment. The prototype of the system will be developed by using Microsoft Access Database Package and Visual Basic Programming Tool. It is essential that the plantation industry move parallel in line with the information age.